Sintesis nanopartikel nikel hidroksida dengan menggunakan tween 20 dan PEG 400 - Yanatra Budi Pramana; M. Sochibul A’lal Ma’arif; Sabdari Bella Chrisdia; Aprilia Isti Triantini; Akhmad Solikin; Krisyanti Budipramana (Universitas PGRI Adi Buana Surabaya, 2022)
In this study we compared the synthesis of nickel hydroxide nanoparticles using two different solutions, namely tween 20 and PEG (Polyethylene Glycol) 400, the electrolysis method used 0.3 M sodium citrate with the addition of tween 20 and PEG 400, using a potential of 25 Volts for 30 minutes. Obtained nickel hydroxide nanoparticles. Scanning electron microscopy (SEM) is used for morphological characterization of the product. Nickel hydroxide nanoparticles added with tween 20 were in the form of nanoflowers, while nickel hydroxide nanoparticles added with PEG 400 were in a spherical shape. Keywords: High Voltage,Electrolysis, Ni(OH)2 nanoparticles